2015
DOI: 10.1089/ast.2014.1203
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Trace Organics in Mars Analog Samples Containing Perchlorate by Laser Desorption/Ionization Mass Spectrometry

Abstract: Evidence from recent Mars missions indicates the presence of perchlorate salts up to 1 wt % level in the near-surface materials. Mixed perchlorates and other oxychlorine species may complicate the detection of organic molecules in bulk martian samples when using pyrolysis techniques. To address this analytical challenge, we report here results of laboratory measurements with laser desorption mass spectrometry, including analyses performed on both commercial and Mars Organic Molecule Analyzer (MOMA) breadboard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…For the elucidation of the chirality of martian analytes, the MOMA gas chromatograph employs one chiral stationary phase that is able to resolve and quantify enantiomers of many different families of organic molecules. Furthermore, the MOMA-LDMS mode of operation does not seem to be affected by the presence of perchlorate in the sample (Li et al , 2015 ); the laser energy deposition pulse is too fast for perchlorates to dissociate and trigger oxidative reactions, but effective enough to desorb organic molecules.…”
Section: The Exomars Rover and Its Pasteur Payloadmentioning
confidence: 99%
“…For the elucidation of the chirality of martian analytes, the MOMA gas chromatograph employs one chiral stationary phase that is able to resolve and quantify enantiomers of many different families of organic molecules. Furthermore, the MOMA-LDMS mode of operation does not seem to be affected by the presence of perchlorate in the sample (Li et al , 2015 ); the laser energy deposition pulse is too fast for perchlorates to dissociate and trigger oxidative reactions, but effective enough to desorb organic molecules.…”
Section: The Exomars Rover and Its Pasteur Payloadmentioning
confidence: 99%
“…[36][37][38] In this context, special attention is currently being devoted to the quest for low molecular weight biomarkers of extinct or extant life on planetary objects beyond Earth. [6,[39][40][41][42] Nonetheless, the few direct LDI studies reported so far have employed equipment that is not suitable for implementation on spacecraft, where requirements concerning weight, size and power consumption are very strict. Over the last 15 years, however, laser ablation/ionization mass spectrometry (LIMS) has re-emerged as an analytical technique suitable not only for laboratory, but also for space applications.…”
Section: Rationalementioning
confidence: 99%
“…These investigations are particularly encouraging for in situ space research where minimal or no sample preparation procedures and no spatial disruption of the analyte prior to the analysis are of prime importance . In this context, special attention is currently being devoted to the quest for low molecular weight biomarkers of extinct or extant life on planetary objects beyond Earth . Nonetheless, the few direct LDI studies reported so far have employed equipment that is not suitable for implementation on spacecraft, where requirements concerning weight, size and power consumption are very strict.…”
mentioning
confidence: 99%
“…This process is based upon empirical comparisons of spectra of mineral matrices with and without organic spikes, built up from simple combinations using pure phases. Previous work has demonstrated that LDI enables detection of trace amounts (ppmw levels) of complex organics at fine scales in mineral matrices, even in the presence of 1 wt % of perchlorate salt (Li et al , 2015 ).…”
Section: Operation Of Moma On the Surface Of Marsmentioning
confidence: 99%